Hypothermia in Victims of the Great East Japan Earthquake: A Survey in Miyagi Prefecture. (12th September 2014) - Furukawa, Hajime; Kudo, Daisuke; Nakagawa, Atsuhiro; Matsumura, Takashi; Abe, Yoshiko; Konishi, Ryota; Yamanouchi, Satoshi; Ishibashi, Satoru; Kobayashi, Masakazu; Narita, Norio; Washio, Toshikatsu; Arafune, Tatsuhiko; et al.
Abstract Objective A survey was conducted to describe the characteristics of patients treated for hypothermia after the Great East Japan Earthquake. Methods Written questionnaires were distributed to 72 emergency medical hospitals in Miyagi Prefecture. Data were requested regarding inpatients with a temperature less than 36ºC admitted within 72 hours after the earthquake. The availability of functional heating systems and the time required to restore heating after the earthquake were also documented. Results A total of 91 inpatients from 13 hospitals were identified. Tsunami victims comprised 73% of the patients with hypothermia. Within 24 hours of the earthquake, 66 patients were admitted. Most patients with a temperature of 32ºC or higher were treated with passive external rewarming with blankets. Discharge without sequelae was reported for 83.3% of patients admitted within 24 hours of the earthquake and 44.0% of those admitted from 24 to 72 hours after the earthquake. Heating systems were restored within 3 days of the earthquake at 43% of the hospitals. Conclusions Hypothermia in patients hospitalized within 72 hours of the earthquake was primarily due to cold-water exposure during the tsunami. Many patients were successfully treated in spite of the post-earthquake disruption of regional social infrastructure.(Disaster Med Public Health Preparedness. 2014;0:1-11)